A compensation claim for vehicle accidents victims in light of the provisions of the unified vehicle insurance policy in the United Arab Emirates (a comparative study) - Abu Obaid, Wail Ibrahim Mahmoud Mohamed (Journal of Economic, Administrative and Legal Sciences, 2022)
The purpose of this study is to identify the claims for compensation for vehicle accidents in the light of the provisions of the United Arab Emirates Common Vehicle Insurance Document. A comparative study between United Arab Emirates law and Egyptian law has used a comparative analytical approach. The study produced a number of results، the most important of which is that the authority of criminal law plays a role in determining liability for a car accident. insured person is insolvent or bankrupt، and the insured person is unable to resort to the insurance company directly. (Insurance Company) Confronting the defenses before the insured، the parties to the litigation or liabilities in the direct litigation are originally tripartite. The defendant is always the insured (Insurance Company) The plaintiff is mostly the injured person but may replace the injured person، such as the beneficiary or the heirs. In any event، the plaintiff is required not to have been compensated for the damage suffered، and another party to the proceedings is the insured person who in some cases has to be brought into it.One of the most important recommendations that the research reached was that the UAE legislator expedite the issuance of the compulsory vehicle insurance law, as the Egyptian legislator did, and the UAE legislator’s call to stipulate a period of time during which the insurer must pay compensation to the injured amicably and without the need to resort to the judiciary under penalty of liability and a fine in the event His failure to comply with this obligation, as did the Egyptian legislator.
Keywords: compulsory vehicle insurance; The rights of the victims of vehicle accidents; the unified vehicle insurance policy (UAE); the insurance company's return to the insured and the cause of the accident